The investigation of N‒dinitrophenyl derivatives of amino acids by electron/chemical ionization using a particle beam interface1. Issue 2 (1999) - Kaußmann Kaußmann, M. M.; Budzikiewicz Budzikiewicz, H. H.
Abstract : The EI and CI mass spectra of DNP‒amino acids and oligopeptides give characteristic mass spectra when a particle beam interface is used for introduction. They differ from mass spectra obtained after direct insertion into the ion source: In the particle beam interface the major part of the molecules suffers degradation by contact with metal surfaces such as decarboxylation and reduction of the nitro groups. The final products are benzimidazole derivatives carrying in 2‒position the residue of the respective amino acid. These products show characteristic fragmentation reactions which allow to identify isomeric amino acids. For DNP‒di‒ and oligopeptides an identification of the N‒terminal amino acid is always possible, that of the C‒terminus with restrictions.